2009
DOI: 10.1590/s0103-97332009000500010
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenic properties of natural rubber latex biomembranes and the serum fraction of Hevea brasiliensis

Abstract: The angiogenic properties of natural rubber were evaluated in this work. We have used the chick chorioallantoic membrane assay (CAM) as a model to investigate the influence of the heating on biological activity in rubber membranes and in non rubber fraction as well. Results showed that natural rubber membranes can induce vascularization. It was observed that angiogenesis activity was maximum when membranes were heated in temperatures between 65 o C and 85 o C, considering a range from 55 o C to 105 o C. The sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 21 publications
(29 reference statements)
1
62
0
3
Order By: Relevance
“…All values were significant for each individual group regarding ABG closure, with no significant differences between groups (Table 6). Preliminary studies have shown the presence of a possible vascular growth factor in Hevea brasiliensis which acts on human tissues, permitting improved vascularization of the temporalis muscle fascia graft from the remaining tympanic membrane by means of its ability to induce angiogenesis 11,12 . The use of the latex biomembrane as a transitory implant in addition to the temporalis muscle fascia graft proved to be biocompatible, causing no increase in infections, otorrhea or otorragy compared to the control group or the silicone membrane group (Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All values were significant for each individual group regarding ABG closure, with no significant differences between groups (Table 6). Preliminary studies have shown the presence of a possible vascular growth factor in Hevea brasiliensis which acts on human tissues, permitting improved vascularization of the temporalis muscle fascia graft from the remaining tympanic membrane by means of its ability to induce angiogenesis 11,12 . The use of the latex biomembrane as a transitory implant in addition to the temporalis muscle fascia graft proved to be biocompatible, causing no increase in infections, otorrhea or otorragy compared to the control group or the silicone membrane group (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…This biocompatibility and the tissue regeneration properties of the natural latex have led to the recognition and liberation of the use of the biomembrane by the Brazilian health regulatory authority ANVISA 5,11,13,14 .…”
Section: A Total Ofmentioning
confidence: 99%
“…The reason behind this is well explored as allergic problems in some sensitive individuals, which cause immediate hypersensitivity, mediated by immunoglobulin E (IgE) antibodies to specific proteins (Hevb1 and Hevb3) in the latex. On the one hand, however, the prevalence of latex allergy in population is believed to be very low 4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…6 Latex and its constituents have been specifically implicated in multiple biological propertiesand it is known to stimulate angiogenic activity, cell adhesion, extracellular matrix formation, and to improve wound healing in skin tissue. 7,8 Ferreira et al (2009), 9 showed that the non-rubber constituents of H. brasiliensis latex are the bioactive fraction responsible for angiogenic properties of this material.Latexconstituents can be separated in three parts when centrifuged at high speed, consisting of the rubber cream, centrifuged serum (C-serum) and the bottom fraction (B-serum). 7,9 The B-serum contains vacuole-like organelles known as lutoids bodies.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Ferreira et al (2009), 9 showed that the non-rubber constituents of H. brasiliensis latex are the bioactive fraction responsible for angiogenic properties of this material.Latexconstituents can be separated in three parts when centrifuged at high speed, consisting of the rubber cream, centrifuged serum (C-serum) and the bottom fraction (B-serum). 7,9 The B-serum contains vacuole-like organelles known as lutoids bodies. C-serum is the phase that contains the soluble substances found in plant cells cytoplasm such as proteins, amino acids, carbohydrates, organic acids, inorganic salts and nucleotidic materials.…”
Section: Introductionmentioning
confidence: 99%